Argument increment stability criterion for linear delta models - Hofreiter, Milan; Zítek, Pavel (Zielona Góra: Uniwersytet Zielonogórski)
Currently used stability criteria for linear sampled-data systems refer to the standard linear difference equation form of the system model. This paper presents a stability criterion based on the argument increment rule modified for the delta operator form of the sampled-data model.
Keywords: delta model; stability criterion; conformal mapping; delta operator; argument increment rule